Pengaruh Substitusi Pecahan Limbah Keramik terhadap Kekuatan Beton K-250 - Pramesta Armanisag Pangestuti; Agustinus Sungsang Nana Patria; Ade Sovia Yahya (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Ceramic waste can be utilized as an alternative construction material to reduce solid waste accumulation and the consumption of natural aggregates. This study aimed to evaluate the effects of ceramic fragments as a partial replacement for coarse aggregate on the slump, unit weight, and compressive strength of K-250 concrete. A laboratory experimental method was applied using 15 × 15 × 15 cm cube specimens with substitution levels of 0%, 5%, 10%, 15%, and 20%. Each mixture consisted of six specimens, giving a total of 30 cubes. The concrete mixtures were designed according to SNI 03-2834-2000 with a water–cement ratio of 0.49 and tested at 7 and 28 days. The results showed that the slump decreased from 7.5 cm in normal concrete to 6.5 cm at the 15% and 20% substitutions. The unit weight declined from 2.440 to 2.284 g/cm³ at the 20% level. The 28-day compressive strengths were 379.50, 340.20, 311.80, 330.10, and 330.60 kg/cm², respectively. Although all mixtures exceeded the K-250 target, the 5% substitution provided the best performance among the ceramic-containing mixtures. Ceramic fragments may therefore be used in limited proportions as coarse aggregate substitutes, provided that adequate quality control is applied.